Implementation Tacit Knowledge, Internal Knowledge on Performance Management: (Systematic Literature Review) - Dharmanto, Agus; Sawitri, Ni Nyoman; Faeni, Dewi Puspaningtyas; Suroso, Sugeng (MultiTech Publisher, 2024)
This paper is to find the results of the implementation of the variables used in this paper which have been used in the research findings, problems and phenomena in this paper as illustrations and solutions from the research findings in the literature. A thorough literature review was conducted as part of the research methodology for this paper. A selection of related scientific articles were collected, analyzed, and reviewed as part of the literature review. The scope of the study was determined based on scores using the PICO framework (population problem, intervention, comparison). The implementation of these three variables already exists, but it is not related to all the variables in one literature in one paper, this paper provides an answer that these variables already exist, and the problems presented above are answered even though they are not optimal and satisfactory in the paper this. The implementation of the three variables in qualitative results is proven and answers problems that are not yet satisfactory.